Use of prophylactic antibiotic in preventing complications for blunt and penetrating chest trauma requiring chest drain insertion: a systematic review and meta-analysis. Issue 1 (22nd February 2019) - Ayoub, Firas; Quirke, Michael; Frith, Daniel
Abstract : Background: Chest drain insertion after chest trauma is often associated with high rate of complications. The use of prophylactic antibiotics in patients with blunt and penetrating chest trauma to prevent empyema and pneumonia after chest drain insertion has been debated. Objective: To analyze the effectiveness of prophylactic antibiotics versus placebo to prevent complications in patients with blunt and penetrating chest injuries who require the insertion of a chest drain. Methods: Pubmed, Embase, and grey literature databases were searched during May 2017 for randomized clinical trails comparing prophylactic antibiotic versus placebo in patients with chest injuries requiring chest drain insertion. Good quality randomized studies which met the inclusion criteria were assessed using the Cochrane Collaboration tool for assessing risk of bias and then were included in the systematic review. A meta-analysis of the included studies was concluded using Stata to analyze the relative risk of empyema and pneumonia in these patients. Results: The study identified 12 randomized studies that included 1263 patients with isolated blunt and penetrating chest trauma. The incidence of empyema after a chest drain insertion was 1% in the antibiotic group and 7.2% in the placebo group. The incidence of pneumonia after a chest drain insertion was 4.4% in the antibiotic group and 10.7% in the placebo group. The use prophylactic antibiotic in those patients was associated with a reduced risk of empyema (relative risk [RR] 0.25; 95% CI 0.13 to 0.49) and pneumonia (RR 0.41; 95% CI 0.24 to 0.71) after chest drain insertion when compared with placebo alone. Conclusion: Prophylactic antibiotic administration in patients with penetrating and blunt chest injuries requiring the insertion of a chest drain was associated with a reduced risk for post-traumatic empyema and pneumonia. Further studies should evaluate the optimal type, dose, and duration of antibiotic given to patients with chest trauma requiring chest drain insertion.